HUBUNGAN JOB INSECURITY, FAKTOR INTERNAL KARYAWAN, DAN FAKTOR INTERNAL ORGANISASI TERHADAP KINERJA KARYAWAN DI PT MANUFAKTUR PADA TAHUN 2023 - Zafira Salsabila (2024)
Due to a decrease in the number of employees, there is a job rotation system. This creates psychosocial stressors which lead to the symptoms of decreased performance. This study aims to determine the factors associated with employee performance at PT Manufaktur, such as job insecurity, internal individual factors (work motivation and individual characteristics) and internal organizational factors (organizational culture and climate). This research was quantitative research with a cross-sectional study design. PT Manufaktur production workers became the study population with a total of 411 employees. By using Lemeshow's formula for the two proportions difference hypothesis test, a minimum sample size of 123 employees was obtained. All samples were selected using a simple random sampling technique. Data collection was conducted by distributing written questionnaires to employees who met the sample criteria. The chi-square test was used for data analysis. The results show that there is no significant relationship between age, sex, education level and work period with employee performance. However, job insecurity, work motivation, organizational culture and organizational climate have a significant relationship with employee performance. Suggestion boxes should be in place so that employees can actively participate in implementing applicable guidelines and expressing constructive input or criticism.